Variability of daily space use in wild boar Sus scrofa. Issue 1 (17th March 2020) - Johann, Franz; Handschuh, Markus; Linderoth, Peter; Heurich, Marco; Dormann, Carsten F.; Arnold, Janosch
Abstract : Wild boar space use and the determinants of its variation are crucial information for understanding wild boar Sus scrofa (L.) ecology and for wild boar management. Wild boar space use has mostly been investigated on broad temporal scales such as annual or seasonal home ranges. Ranges can vary depending on the observed timespan and on the temporal scales considered. The factors that affect space use variation can also depend on temporal scales. In this study, we present an analysis of time series of daily ranging behaviour in wild boar. Using GPS‐telemetry, we tracked 46 collared wild boars in southwest Germany. With the collected data, we calculated 6716 daily ranges of individuals based on at least 18 daily locations with near hourly location intervals. We compared three home range estimation methods and fitted multivariate models to assess the effects of the landscape, temporal and climatic factors or individual traits on the daily range size. The daily range size varied significantly in the course of the year. The smallest daily ranges were covered from April to July, whereas the largest were covered in November and December. However, if the same days of the year are compared, lower temperatures reduced the size of daily ranges. Additionally, individual variation, social class, snow height, land use and elevation had a significant effect on the size of daily ranges. Our results may be useful for planning protected areas, for monitoring wild boar populations, attributing agricultural damages to wild boar groups and for searching wounded or escaped animals. Moreover, the knowledge of daily used space may help to identify African swine fever (ASF) infection paths or design measures to reduce ASF risk including carcass removal, fencing projects or demarcation of management zones.